Comparative Analysis of Performance of Mat Foundations in Non-liquefiable and Liquefiable Soil - Tukashaba, Shafan; Ping, Yi (East African Nature and Science Organization, 2024)
This study investigates the behavior and performance of mat foundations in non-liquefiable and liquefiable soil, aiming to provide insights for engineers under soil liquefaction conditions. Through finite element analyses, the study explores shallow foundation design complexities, assesses the bearing capacities of mat foundations under liquefaction soil characteristics, and offers data-driven design strategies for such conditions. The findings on mat foundations in liquefiable soil reveal that iterative dimension adjustments lead to significant enhancements in bearing capacity, hence exceeding the load-bearing capacity in non-liquefiable soil that is used as benchmark. The modification factors range from 2.4 to 2.6 times the original dimensions verified to be effective. These results emphasize the role of tailored design adjustments and numerical designs in solving diverse soil settings and enhancing structural safety, performance, and integrity in foundation design, especially in challenging soil conditions with liquefaction